2018
DOI: 10.5539/cco.v7n2p23
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the Biozorb Device for Radiation Planning in Oncoplastic Surgery

Abstract: Purpose: With the extent of breast tissue manipulation using oncoplastic surgical techniques, there lies a challenge in marking the tumor bed for adjuvant radiation therapy planning. Two competing techniques in doing so exist and involve the traditional placement of surgical clips in the surgical tumor bed or the newer technique of placing a Biozorb marker in the tumor bed. Our goal was to perform a cost-utility assessment to see which tumor bed marking approach is more cost-effective. Based on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A smaller marker, or avoidance of utilization of the marker is recommended if a paucity of overlying tissue exists (36). Biozorb  has not demonstrated value given its relative high cost and lack of clinical advantage scientifically over the use of surgical clips (38).…”
Section: Biozorb mentioning
confidence: 99%
“…A smaller marker, or avoidance of utilization of the marker is recommended if a paucity of overlying tissue exists (36). Biozorb  has not demonstrated value given its relative high cost and lack of clinical advantage scientifically over the use of surgical clips (38).…”
Section: Biozorb mentioning
confidence: 99%
“…However, breast surgeons have used this bioresorbable device with hopes that it would also assist in filling the tissue void and improving cosmetic results. Published clinical studies indicate that both surgeons and patients have been uniformly dissatisfied with BioZorb since this implant is relatively expensive, does not significantly improve outcomes, and gives rise to a hard, palpable lump that lasts for up to 2.8 years and causes patient discomfort 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Cost analysis is needed as previous studies have shown cost benefit to clips over 3DBM in identifying the tumor bed for radiation. 5 Additionally, operative time comparisons and long-term effects must be considered. In conclusion, TR with use of 3DBM may allow surgeons more basic oncoplastic options to improve patient satisfaction.…”
mentioning
confidence: 99%